Environmental policies for a multifunctional agricultural sector in open economies - Peterson, Jeffrey M.; Boisvert, Richard N.; de Gorter, Harry (My University, 2013)
This paper derives the efficient set of policies for a multifunctional agriculture and relates them to trade. In general, efficiency cannot be achieved through simple output subsidies, but the efficient policies to move closer to socially optimal levels of multifunctional, non-commodity outputs may also change commodity output levels. Accounting for international price effects, large importing and exporting nations have incentives to favour subsidies for non-commodity outputs and oppose them, respectively, regardless of the true value of these agriculturally-related public goods. The policy incentives are illustrated through a stylised simulation of United States’ agriculture.
Keywords: Multifunctionality; Agricultural trade; Environmental policy